NEUROLOGICAL CHANGES IN POST-COVID SYNDROME - Djumaeva Nasiba Sobirovna (Лучшие интеллектуальные исследования, 2024)
INTRODUCTION. The causative agent of the new coronavirus infection SARS-CoV-2 is the pathogen responsible for the development of COVID-19, it is a multi-organ disease with a wide range of symptoms.[1,6,7] The completion of the acute phase of coronavirus infection varies in duration. This can be learned from dynamic monitoring of millions of patients who have been ill over the past 2 years. In a third of patients, the acute inflammatory period of the disease can pass without any consequences.[7,8] When the disease has severe clinical manifestations, most patients experience various clinical signs and residual complications. Often these residual complications are proportional to the severity of the disease; in some cases, the consequences of the disease and residual symptoms do not depend on the period of acute inflammation.[1,2,4] This is not the problem we want to focus on. In a certain proportion of patients, residual complications and secondary syndromes affect the quality of life for several months and require special attention and special correction. The symptoms of these adverse events are very diverse, and cover dysfunction of many organs and systems and require the formation of a polymorphism of secondary and delayed complications. The term "polymorph" can have any phenotypic basis (morphological, physiological, biochemical, behavioral including the trait can be used at the genetic level. [8,9] COVID-19 has caused unprecedented numbers of cases and deaths worldwide, and at the same time, there were many reports of subacute and long-term consequences for many organs and systems.